Noise level analysis in adult intensive care unit - Christofel, Helen Katharine; Madeiras, Joselene Gomes; Bertolini, Sonia Maria Marques Gomes; Oliveira, Juliana Maria de (Rev Rene, 2016)
Objective: to analyze the noise level in adult intensive care unit. Methods: a quantitative study, in which the sound levels of the intensive care unit have been assessed by means of a decibel meter. Results: comparing the groups, there was a reduction in noise levels in both periods studied, but only in the afternoon there was a statistically significant difference (p<0.05). The health professionals pointed out that the unit had moderate noise, coming mainly from equipment and professionals. Conclusion: adjusting the ventilator alarms contributed to the reduction of noise levels in the unit, and there was the perception that it is a moderate noise environment, although the noise levels in decibels observed were above the recommended values.